PRAKTIK GADAI SEPEDA MOTOR PERSPEKTIF HUKUM ISLAM DI DUSUN MELATI KECAMATAN TEBAS - Rosana, Mayang; Rahayu, Riska (Islamic Banking & Economic Law Studies (I-BEST), 2023)
This research is motivated by the deduction of the nominal value at the beginning of the agreement and there is additional money if Rahin is late paying his loan to the Murtahin. The focus of the problem in this research is how to practice motorbike pawining in Village Melati Districts Tebas which is then reviewed from the perspective of Islamic law. This research uses a type of qualitative research that is field research. Data sources used are primary data sources and secondary data sources. The result of this study are pawn practices carried out in Melati Village done orally, and at the beginning of the agreement there is a deduction of the nominal value and if  Rahin is late paying the loan then there will be additional money given by Murtahin to Rahin. If seen from the principles of Islamic law, the implementation of motorbike pawning in Melati Village not in accordance with the principle of pawning in Islam. This is due to the deduction of the face value at the beginning of the agreement and the existence of additional money if Rahin cannot pay the loan on time. This causes loss and compulsion  for Rahin over the provisions made by Murtahin.